Aryl- and alkyl-phosphorus-containing flame retardants induced mitochondrial impairment and cell death in Chinese hamster ovary (CHO-k1) cells. (November 2017) - Huang, Chao; Li, Na; Yuan, Shengwu; Ji, Xiaoya; Ma, Mei; Rao, Kaifeng; Wang, Zijian
Abstract: Phosphorus-containing flame retardants (PFRs) are increasingly in demand worldwide as replacements for brominated flame retardants (BFRs), but insufficient available toxicological information on PFRs makes assessing their health risks challenging. Mitochondria are important targets of various environmental pollutants, and mitochondrial dysfunction may lead to many common diseases. In the present study, mitochondria impairment-related endpoints were measured by a high content screening (HCS) assay for 11 selected non-halogen PFRs in Chinese hamster ovary (CHO-k1) cells. A cluster analysis was used to categorize these PFRs into three groups according to their structural characteristics and results from the HCS assay. Two groups, containing long-chain alkyl-PFRs and all aryl-PFRs, were found to cause mitochondrial impairment but showed different mechanisms of toxicity. Due to the high correlation between cell death and mitochondrial impairment, two PFRs with different structures, trihexyl phosphate (THP) and cresyl diphenyl phosphate (CDP), were selected and compared with chlorpyrifos (CPF) to elucidate their mechanism of inducing cell death. THP (an alkyl-PFR) was found to utilize a similar pathway as CPF to induce apoptosis. However, cell death induced by CDP (an aryl-PFR) was different from classical necrosis based on experiments to discriminate among the different modes of cell death. These results confirm that mitochondria might be important targets for some PFRs and that differently structured PFRs could function via distinct mechanisms of toxicity. Graphical abstract: Highlights: Mitochondrial impairment induced by PFRs was observed in CHO-k1 cells. THP (an alkyl-PFR) induced a caspase-mediated apoptosis in CHO-k1 cells. The cell death induced by CDP (an aryl-PFR) was not traditional apoptosis or necrosis.